Long-Term Outcomes of All-Arthroscopic Pre-Tied Suture Device Triangular Fibrocartilage Complex Repair - Sarkissian, Eric J.; Burn, Matthew B.; Yao, Jeffrey (Journal of Wrist Surgery, 2019)
Background A pre-tied suture device has been utilized for all-arthroscopic peripheral triangular fibrocartilage complex (TFCC) repairs with promising early clinical results.Purpose The purpose of this study was to evaluate long-term functional outcomes of these repairs.Patients and Methods A retrospective review of patients undergoing arthroscopic TFCC repair was performed. Inclusion criteria were the Palmer type 1B TFCC tears diagnosed on arthroscopy and repaired using the all-arthroscopic pre-tied suture device. Patients with any evidence of concomitant wrist injury at the time of surgery, history of prior wrist surgery, or nonrepairable and nonperipheral TFCC tears were excluded. Postoperative complications, range of motion, grip strength, and outcome assessments were recorded for each patient.Results Eleven patients (mean age, 36 years; range, 20–64 years) satisfied our inclusion criteria and comprised the study cohort. The mean follow-up period was 7.0 years (range, 4.3–10.9 years). Mean range of motion of the wrist revealed flexion of 76 ± 11 degrees and extension of 73 ± 12 degrees. Mean grip strength was 98 ± 15% of the nonsurgical extremity. QuickDASH, modified Mayo, and patient-rated wrist evaluation (PRWE) average scores were 9 ± 8, 80 ± 6, and 12 ± 12, respectively. No surgical complications were observed and no patient required any further surgical intervention.Conclusions Our cohort of patients following all-arthroscopic pre-tied suture device repair of isolated Palmer type 1B TFCC tears demonstrated excellent clinical function at a mean follow-up of 7 years. These findings indicate that the pre-tied suture device is a reliable, safe, effective, and most importantly, durable treatment option for repair of peripheral TFCC tears.Level of Evidence This is a Level IV, therapeutic study.
Keywords: triangular fibrocartilage complex (TFCC); pre-tied suture; all-arthroscopic repair